2021
DOI: 10.1002/ppul.25321
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards involving children in decision‐making surrounding lung transplantation

Abstract: Background: Medical care has shifted from a paternalistic model towards one centered around patient autonomy and shared decision-making (SDM), yet the role of the pediatric patient in decision-making is unclear. Studies suggest that many children with chronic disease are capable of making medical decisions at a young age, yet no standardized approaches have been developed for involving children in these decisions.Methods: This is a single-center survey study investigating the attitudes of pediatric pulmonologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
(143 reference statements)
0
4
0
Order By: Relevance
“…Children's participation in shared decision-making was diverse and ranged from no involvement to being the main decision-maker (1,6,, as described in table 1. Children's participation was categorised into 'major' and 'minor' decisions.…”
Section: Children's Experiences In Shared Decision-makingmentioning
confidence: 99%
See 3 more Smart Citations
“…Children's participation in shared decision-making was diverse and ranged from no involvement to being the main decision-maker (1,6,, as described in table 1. Children's participation was categorised into 'major' and 'minor' decisions.…”
Section: Children's Experiences In Shared Decision-makingmentioning
confidence: 99%
“…The children reported that their perceptions of decision-making as they could either facilitate or obstruct a child's participation (8,12,19,34). Children's involvement in decision-making could be improved by knowing the related facilitators and barriers from the healthcare professionals' and parents' perspectives (1). Thus, understanding healthcare professionals' and parents' views on children's participation in shared decision-making is crucial.…”
Section: Children's Preferences For Participation In Shared Decision-...mentioning
confidence: 99%
See 2 more Smart Citations